"We now fly": Perspectives of adults who are blind with guide dogs trained for running. (September 2019) - Lieberman, Lauren J; Haibach-Beach, Pamela S; Sherwood, Jenna; Trad, Alyssa
Individuals with visual impairments lead less active lifestyles than their sighted counterparts. Reduced physical activity in this population can be attributed to a lack of opportunities combined with fewer intervention opportunities, less experience in sport and recreational activities, and decreased perceived motor competence. Furthermore, individuals with visual impairments report lower values in all domains of quality of life when compared with their sighted counterparts. Therefore, it is imperative that opportunities are developed to increase self-determination leading to higher levels of physical activity for individuals with visual impairments. Running is a popular physical activity for active individuals; however, there are many barriers to running for individuals with visual impairments. To increase these opportunities, a school for guide dogs has recently started training guide dogs to run. The purpose of this study was to determine the perspectives of adults with visual impairments on their experiences running with trained running guide dogs. Ten adults who are blind were interviewed on phone by two researchers. Qualitative research questions were validated by two adults who are blind, three specialists in adapted physical education, and one guide dog trainer. Interviews were transcribed, and themes were extracted by three of the authors. The four major themes that emerged from this research study were (1) running guide dogs' contribution to mental and physical health, (2) independence as a result of running with a guide dog, (3) The dog is key to increased/improved running, and (4) barriers and supporters to running. Our results indicate that there are numerous positive effects that a running guide dog has on the health, independence, and quality of life of individuals who are blind or visually impaired. The results indicated that making running guide dogs available could provide increased self-determination for adults who choose to take advantage of this program leading to a healthier lifestyle.